PENGARUH EFEKTIVITAS PELATIHAN, BUDAYA KERJA, INOVASI TERHADAP EFEKTIVITAS KERJA SURVEYOR PT SUCOFINDO (PERSERO) CABANG BATAM - Sajiyo Sajiyo (Ensiklopedia of Journal, 2019)
This study aims to determine the effect of training effectiveness, work culture, and innovation on the effectiveness of the work of surveyors. This study uses a quantitative approach using a survey method. Path analysis was used to analyze the data collected. The unit of analysis of this research is the surveyor on Sucofindo PT (Persero) Branch Batam. The results showed that the effectiveness of the surveyor directly influenced by training, workplace culture, and innovation. The study also found that innovation is influenced by training and work culture. Based on these findings it can be concluded that any changes are made to the effectiveness of the surveyor is influenced by training, work culture, and innovation. Therefore, the effectiveness of the surveyor, training, workplace culture, and innovation can be taken into consideration in strategic planning for the development of human resources of a company.